Educational Strategies from the Perspective of the Quran - Sayyed Abulqasem Musavi; Nabiyollah Sadrifar (اخلاق وحیانی, 2013)
The holy Quran has been revealed as a Divine scripture and a standing miracle for the education and guidance of mankind and it is because of this property of the Quran (i.e. guidance) that the verses of the Quran have been studied in this paper to identify the best educational strategies and methods from the perspective of the Quran. These strategies have been categorized into three main strategies in this paper; although other categorizations are also possible. Thus, the present paper analyzes the educational strategies in three separate categories: the first strategy is the cognitive-intuitive strategy. This strategy addresses, the Quranic verses, whose purpose is to address the issues of the origin, the end and the reason of man’s creation, and by directing mankind towards contemplation, remembering the resurrection, paying attention to Allah’s bounties and learning from the mistakes of the people in the past this strategy attends to such cognition and intuition. The second strategy is the attitudinal strategy. This strategy attends to those statements in the Quran that fuel man’s enthusiasm to act. The cultivation of faith, fostering love and affection, penance, premonition, glad tiding, reward and punishment are among the methods employed by this strategy. Yet, the third strategy which has been attended to in the Quran is a set of behavioral strategies which seek to guide those under education. Presenting moral-educational examples in practice, creating role models, respecting the personality of those being educated, admonition, tests and afflictions are but some of the methods employed in this strategy.